Kebijakan Cash Holding Pada Perusahaan Sektor Consumer Cyclicals di Indonesia - Krisdiana, Karina Nindya; Harlina Meidiaswati (Jurnal Ilmu Manajemen, 2024)
This research aims to determine the effect of cash flow, dividends, market-to-book ratio, net working capital, leverage and Z-score on cash holding in consumer cyclical sector companies listed on the Indonesia Stock Exchange for 2018-2022. The type of data used is quantitative data sourced from secondary data. The population comprises consumer cyclical sector companies listed on the Indonesia Stock Exchange from 2018 to 2022. The sampling technique used purposive sampling, and 23 companies were obtained as samples. The research results show that cash flow, market-to-book ratio, and net working capital have a significant and positive effect on cash holding. High cash flow indicates that cash inflow is greater than cash outflow, thus allowing the company to hold and use cash to finance its operational activities. The market-to-book ratio indicates investment opportunities for the company, opens up easy access to capital markets and allows for easy acquisition of additional funds. Excess funds saved by the company will increase cash holdings. An increase in net working capital indicates an increase in cash balances because companies with high liquidity generally hold large amounts of cash. On the other hand, the Z-score shows a significant and negative influence on cash holding. A high Z-score value indicates that the company is in a safe zone and does not need to hold much cash because its financial condition is stable. Meanwhile, dividends and leverage do not show a significant influence on cash holding.